Comparison of autologous and allogeneic stem cell transplantation for patients with Philadelphia chromosome-positive acute lymphoblastic leukemia. Issue 1 (1st January 2021) - Lyu, Mengnan; Jiang, Erlie; He, Yi; Yang, Donglin; Ma, Qiaoling; Pang, Aiming; Zhai, Weihua; Wei, Jialin; Huang, Yong; Zhang, Guixin; Zhang, Rongli; Feng, Sizhou; et al.
ABSTRACT: Objectives: To analyze the outcomes of patients who received autologous stem cell transplantation (auto-SCT), matched sibling donor stem cell transplantation (MSD-SCT) and haploidentical stem cell transplantation (haplo-SCT) and provide the basis for the choice of transplantation method in Philadelphia chromosome-positive acute lymphoblastic leukemia (Ph+ ALL). Methods: We retrospectively investigated the outcomes of 119 adult patients with Ph+ ALL in our center. The overall survival (OS) rate, leukemia-free survival (LFS) rate, cumulative incidence of relapse (CIR) rate, non-relapse mortality (NRM) rate and the impact of achievement of complete molecular response (CMR) within 3 months and sustaining CMR up to transplantation (s3CMR) on transplantation method were explored. Results: The estimated OS, LFS, CIR and NRM rates at 3 years were not significantly different among three groups ( p  =   0.960, 0.917, 0.375 and 0.096, respectively). For the 65 patients who achieved s3CMR, there was no significant difference in OS (84.5% vs 72.5% vs 100%, p  =   0.374), LFS (75.2% vs 64.5% vs 83.3%, p  =   0.668), CIR (17.2% vs 8.1% vs 16.7%, p  =   0.583) and NRM (3.1% vs 23.4% vs 0%, p  =   0.055) among auto-SCT group, MSD-SCT group and haplo-SCT group. However, in patients who did not achieve s3CMR, auto-SCT recipients tended to have higher CIR (60% vs 33.2% vs 24.0%, p  =   0.013) than the allo-HSCT group. Conclusions: Auto-SCT with maintenance therapy after HSCT appears to be an attractive treatment option for patients with Ph+ ALL especially for those whose s3CMR was kept up to transplantation. For non-s3CMR patients, allogeneic transplantation may be more effective from lower relapse.